AB0622 ASSOCIATIONS WITH DIGITAL PITTING IN SYSTEMIC SCLEROSIS: A RETROSPECTIVE ANALYSIS. (2nd June 2020) - Vivekanantham, A.; Dinsdale, G.; Heal, C.; Manning, J.; Herrick, A.
Abstract : Background: Digital pitting, the loss of tissue at the fingertip, is a cardinal feature of systemic sclerosis (SSc), contributing 3 of the 9 required points to fulfil the 2013 ACR/EULAR classification criteria. However, research into digital pitting has been scarce, despite it being painful and impacting on hand function. Objectives: To identify factors associated with digital pitting in patients with SSc. Methods: This was a retrospective analysis of data from patients with SSc attending a tertiary referral centre. Patients were subdivided into those with and without digital pitting, as recorded at their last documented attendance. The following variables were analysed: age, gender, age at Raynaud's onset, age at SSc onset, limited/ diffuse cutaneous subtype, history of intravenous (IV) vasodilators, amputations, debridements and autoantibody status (anti-RNA polymerase, anti-Scl70, anti-centromere and anti-RNP). Results: Data were available from 713 patients with SSc. Digital pitting was present in approximately half of these patients (n=362, 51%). Table 1 summarises their characteristics. From the univariable analysis (Table 2 ), gender (female, p=0.02), age at Raynaud's onset (p<0.001), age at SSc onset (p<0.001), IV vasodilators (p<0.001), amputations (p<0.001), debridements (p<0.001), anti-RNA polymerase (p=0.01), anti-Scl70 (p=0.05) and anti-centromere (p=0.05) were found to be significantly associated (anti-RNA polymerase negatively (p=0.20)) with digital pitting (p≤0.05). Further analysis adjusting the p value for multiple testing (Bonferroni adjustment, p≤0.0036) found age at Raynaud's onset, age at SSc onset, history of IV vasodilators, amputations and debridements to be significantly associated with digital pitting. Conclusion: The results from this exploratory study in a large cohort of SSc patients provide valuable insights into factors associated with digital pitting. Patients with digital pitting often have an earlier onset of Raynauds and of SSc and significantly more debridements/amputations, suggesting that digital pitting is associated with vascular disease severity. Our findings indicate the need for further research investigating pathophysiology of digital pitting, to inform development of preventative treatment strategies. Disclosure of Interests: None declared